Polygonal approximation of digital planar curves through break point suppression - Carmona-Poyato, A.; Madrid-Cuevas, F.J.; Medina-Carnicer, R.; Muñoz-Salinas, R. (Pattern recognition, 2010)
This paper presents a new algorithm that detects a set of dominant points on the boundary of an eight-connected shape to obtain a polygonal approximation of the shape itself. The set of dominant points is obtained from the original break points of the initial boundary, where the integral square is zero. For this goal, most of the original break points are deleted by suppressing those whose perpendicular distance to an approximating straight line is lower than a variable threshold value. The proposed algorithm iteratively deletes redundant break points until the required approximation, which relies on a decrease in the length of the contour and the highest error, is achieved. A comparative experiment with another commonly used algorithm showed that the proposed method produced efficient and effective polygonal approximations for digital planar curves with features of several sizes.